Legal Protection for Esports Athletes Against Freeze Contract Clauses in Employment Relationships - Charomain, Mochammad Imam; Gunadi, Ariawan (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The rapid expansion of the esports industry in Indonesia has not been accompanied by adequate legal certainty regarding employment relationships between athletes and teams, thereby creating opportunities for detrimental contractual practices, including freeze contracts that restrict athletes’ mobility and fundamental rights. This study aims to (1) identify forms of workers’ rights violations arising from the implementation of freeze contracts and (2) assess the adequacy of the existing regulatory framework—including PBESI Regulation Number 034/PB-ESI/B/VI/2021, the Sports Law, and the Manpower Law—in providing legal protection for esports athletes. This study employs a normative juridical method using statutory, conceptual, and case-based analytical approaches. The findings indicate that freeze contracts have the potential to violate the rights to freedom of employment, income security, and equality within the employment relationship. Moreover, the current regulatory framework does not specifically address employment protection for esports athletes. In conclusion, regulatory reform and strengthened contract oversight mechanisms are required to ensure effective and equitable legal protection for athletes.